Assessment on the quality on drinking wells exposed to different degrees of submergence during flood in Kelantan - Ab. Rahman, Hariz Azhar; Ibrahim, Noor Azlina; Abdul Hamid, Azzmer Azzar; Tengku Abdul Hamid, Tengku Haziyamin (2016)
The recent (2014) unprecedented and extraordinary flooding in the several states in the East coast of Peninsular Malaysia (Kelantan, Terengganu and Pahang) had caused overwhelming damages both to residential, commercial and other infrastructures. The overflowing of flood waters had spill into or exchange with local drinking wells and these had culminated in different degrees of changes in both the physicochemical and biological properties of the well’s water. In this study, sampling strategy based on different submerging conditions of well in Kelantan were used in assessing the degree of flood induced changes. A total of 65 wells selected from 13 station scattered around Sungai Kelantan basin and estuary regions were sampled for pH, Total Dissolved solid (TDS), Total Suspended solid (TSS) and microbial contamination (coliform count, CFU/100ml). Most of the samples (95%) from Kelantan’s well showed positive on coliform test after flood. About 7 out of 65 samples (11.1%) showed TDS values >400µS/cm; meanwhile 19 samples (29.2%) recorded turbidity (TSS) beyond 7.0 NTU. Statistical non-parametric tests were carried out on independent groups to evaluate whether if the wells were significantly affected by its location in the Sg. Kelantan basin; or if it was submerged or not by the flood water. Both degree of submergence and well location have no influence on the degree of contamination. Since there were contaminations in non-submerged wells (eg. Machang, Temangan), existing pre-flood contamination could have contributed to variable trend of contamination being observed. In addition, wells exposed to different degree of submergences also showed no difference in the total dissolved solid (TDS) and total suspended solid (TSS). Interestingly, the physicochemical properties of the well water were shown to have effected by the geographical location; the TDS (at P<0.05) and TSS (at P<0.01), respectively. Well water from Sg. Kelantan estuary (Wakaf Baharu, Bachok, Pantai Cahaya Bulan, Rantau Panjang and Pengkalan Chepa) showed to have higher TDS (mean of 241.2 µS/cm ±159.5 SD) and TSS (8.04 NTU ± 6.53 SD) values compared to those from inner basin (Jeli, Tanah Merah, Kuala Krai, Pasir Puteh, Machang and Temangan) with lower mean for TDS (at 156.3 μS/cm ± 88.9 SD); and TSS (2.90 NTU ±2.46 SD). Despite of the flood water was not directly resulted in changes to the well water, it could have enhanced the transmission of existing contamination that already present in the well. Even though the degree of submergence has no influence on the contamination in Kelantan’s well during post flood period, the well location could still provide some information on the physicochemical quality of the well. Therefore, different well locations will be subjected to different changes and safety risk potential after flood.